Environmental Valuation and Greening the National Accounts : Challenges and Initial Practical Steps - World Bank (Washington, DC, 2013)
The national accounts are the single most important source of information about the economy, and are widely used in all countries to assess economic performance and for policy analysis. However, the national accounts have a number of well-known shortcomings when it comes to treatment of the environment. For example, while the income from harvesting timber is recorded in national accounts, the simultaneous depletion of natural forest assets is not; perhaps more importantly, essential life-support services provided by forest ecosystems are not explicitly recognized at all. Environmental accounts 'greening the national accounts' have been developed to address the shortcomings of the national accounts, but valuation of environmental services has been controversial.The development of methods to value environmental goods and services continues to evolve apace. In an increasing number of countries, the practical uptake of these methods has accelerated in numerous areas of public policy that have environmental consequences. One policy related domain, however, where this uptake has been largely conspicuous by its absence is national accounting. In this paper, we hope to make the case that there is an opportunity to address this situation.